Use of the sludge obtained from the electrocoagulation process of pumping waters of fishmeal factories for feeding Tenebrio molitor larvae - Aguilar Ascón, Edwar (2023)
Sludge residue from pumping water treatment obtained by electrocoagulation process (LEC) in fishmeal factories, was used as a feeding ingredient for Tenebrio molitor larvae. LEC was conditioned by three bioprocesses: fermentation with Lactobacillus casei, fermentation with Sacharomyces, and hydrolysis with pancreatin enzymatic mixture. Soybean isolate was used as a control. Larvae consuming LEC-containing diets presented a higher weight gain rate than the controls. The proximal larvae dry basis composition values of fat, ash, and protein (37.2% ± 2%, 3.9% ± 0.4%, and 50.2% ± 4.9%, respectively) did not present significant intergroup differences. LEC contained 4.2% aluminum and its conditioning through fermentation with lactic bacteria reduced its bioavailability in the larvae, with values similar to those of controls (3.9 ± 0.7 µg Al/g). The iron content in LEC-fed larvae was higher than that in the control group, while their fatty acid profile was only slightly different. These initial results with LEC, which organic material is difficult to hydrate and assimilate, suggest its suitability as a protein source and attractant for a faster growth of T. molitor larvae.